DESIGNING AND DEVELOPING SEMESTER TEST AT SMP N 1 SINTUK TOBOH GADANG PADANG PARIAMAN - Susi Karmila (ELT-Lectura, 2018)
The purpose of this research was to determine how an English teacher design andevaluate the semester test. This research was done in SMP N 1 Sintuk Toboh Gadang.One of the ways through which feedback can be obtained from the learners on whatthe teachers had taught them is an evaluation. Students’ achievement in a particularcourse of study can be determined through evaluation. This work observed variousaspects of ordinary level English in which students’ achievement are often assessedwith a view to assisting students in overcoming problems often encountered duringsuch tests and evaluations. Based on the results of observation and interviews withEnglish teachers at the school, explained that for designing the semester test Englishlanguage teachers should be used to assess the degree to which students have learnedwhat they should have learned and provided a vehicle for providing students feedbackabout how well they have learned the material. To solve the problem English teacherdesign and evaluate the semester test by using the grating to help students.